The economic significance of the notion of food security, native and foreign methods of determination. (Journal of Economic Research & Business Administration, 2016)
Food security is a prerequisite for sustainable economic and social de velopment of the country as a whole and individual regions of the world. Therefore, the problem of food security is one of the main tasks pravitelst vovami countries and international organizations are now.Therefore, this article discusses the various approaches to the defini tion of food security, food safety aspects are considered. The paper pres ents the definition of foreign and domestic scientists dealing with food safety and food security.
Keywords: food security; globalization; integration; agriculture; com petitiveness; agricultural products; production.